Surface‐Functionalized Electrospun Titania Nanofibers for the Scavenging and Recycling of Precious Metal Ions. Issue 20 (23rd September 2016) - Dai, Yunqian; Formo, Eric; Li, Haoxuan; Xue, Jiajia; Xia, Younan
Abstract: Precious metals are widely used as catalysts in industry. It is of critical importance to keep the precious metal ions leached from catalysts at a level below one part per million (ppm) in the final products and to recycle the expensive precious metals. Here we demonstrate a simple and effective method for scavenging precious metal ions from an aqueous solution and thereby reduce their concentrations down to the parts per billion (ppb) level. The key component is a filtration membrane comprised of titania (TiO2 ) nanofibers whose surface has been functionalized with a silane bearing amino or thiol group. When operated under continuous flow at a rate of 1 mL min −1 and at room temperature, up to 99.95 % of the Pd 2+ ions could be removed from a stock solution with an initial concentration of 100 ppm. This work offers a viable strategy not only for the removal of precious metal ions but also for recovering and further recycling them for use as catalysts. For example, the captured Pd 2+ ions could be converted to nanoparticles and used as catalysts for organic reactions such as Suzuki coupling in a continuous flow reactor. This system can be potentially applied to pharmaceutical industry and waste stream treatment. Abstract : Must have the precious : Precious metals are widely used as catalysts in industry. It is of critical importance to keep the precious metal ions leached from catalysts at a level below one part per million (ppm) in final products and to recycle the expensive metals. Precious metal ions were scavenged by surface‐functionalized electrospun TiO2 nanofibers and further recycled for use as catalysts. This system can be potentially applied in pharmaceutical industry.